1976
DOI: 10.1021/j100561a005
|View full text |Cite
|
Sign up to set email alerts
|

Photoperoxidation of unsaturated organic molecules. 16. Excitation energy fission

Abstract: Is the intensity of the high overtones you see caused by the electrical anharmonicity of the bonds being stretched? B. R. Henry. We have actually looked on the problem more from the point of view of mechanical anharmonicity than of electrical anharmonicity, but in this region of the spectrum it may be impossible to disentangle one from the other. The detailed intensity problem in normal mode language is one that I think we haven't solved, and to my knowledge, neither has anyone else. S. J. STRICKLER. I do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 1 publication
2
11
0
Order By: Relevance
“…Thus, Brauer and Wagner first demonstrated that both the TI state and 02('Ag) may be formed in the fluorescence quenching by 0, and that the maximum value of Qa can be 2 (72). This important result was confirmed by both authors in the investigation of the self-sensitized photooxygenation of heterocoerdianthrone (73), by Stevens and Ors in their re-evaluation of previous rubrene photooxygenation data (74), and by Wu and Trozzolo (75). Brauer et al (76) and Usui et al (77) determined by the same technique for a larger number of aromatic compounds 1 5 f: + S A 5 2.…”
Section: Singlet Sensitizationsupporting
confidence: 60%
See 1 more Smart Citation
“…Thus, Brauer and Wagner first demonstrated that both the TI state and 02('Ag) may be formed in the fluorescence quenching by 0, and that the maximum value of Qa can be 2 (72). This important result was confirmed by both authors in the investigation of the self-sensitized photooxygenation of heterocoerdianthrone (73), by Stevens and Ors in their re-evaluation of previous rubrene photooxygenation data (74), and by Wu and Trozzolo (75). Brauer et al (76) and Usui et al (77) determined by the same technique for a larger number of aromatic compounds 1 5 f: + S A 5 2.…”
Section: Singlet Sensitizationsupporting
confidence: 60%
“…The condition Δ E ST < E Δ = 94 kJ mol −1 is imperative but not sufficient for efficiencies f S Δ = 1. This was first noted by Stevens and Ors, whose re‐evaluation of previous Q po data led to values of f S Δ + S Δ = 1.0 and 1.2 for 9,10‐dimethyl‐1,2‐benzanthracene and tetracene in BNZ, respectively (74). For both compounds, Δ E ST < 94 kJ mol −1 holds true; however, upper excited triplet states T n lie below S 1 in both cases.…”
Section: Discussionmentioning
confidence: 71%
“…PAP 40:5-11 58 1 converted to singlet oxygen according to an unusual process (Santamaria, 1981). In addition, the singlet state of highly fluorescent molecules has been shown to produce singlet oxygen directly (Wu and Trozzolo, 1979;Stevens and Ors, 1976;Streichen and Foote, 1981). Thus various types of oxidation may occur simultaneously.…”
Section: (3)mentioning
confidence: 99%
“…Kenner and Khan [6][7][8][9] finally established the TSA mechanism {2} beyond doubt, and they concluded [6] that the delayed fluorescence observed by them was of the same type as that observed by Kautsky and Muller [2]. The importance of reaction {1} is now also firmly established due to the experimental investigations by Brauer et al [10][11][12] and others [13][14][15][16][17][18].…”
Section: {2}mentioning
confidence: 96%